Kritik Ekologi dalam Cerita Lisan “Sedah Wong” Berbahasa Bali di Desa Adat Kesiman - Putri Prasista, Ni Putu; Puspawati, Luh Putu; Widhiarcani Matradewi, Ni Ketut (Humanis, 2025)
This research is entitled "Ecological Criticism in the Oral Stories of Sedah Wong in the Kesiman Traditional Village". This research aims to describe the literary ecology contained in it. This research uses the theory of literary ecocriticism. The listening method and proficient method with recording techniques, note-taking techniques as well as literal and idiomatic translation techniques were used in the data collection stage. Informal and formal methods are used in presenting the results of data analysis using deductive and inductive techniques. The results of this research are that oral stories contain a literary ecology consisting of: (1) Pastoral narratives including bucolic elements and arcadia construction elements. (2) Apocalyptic narratives include hero characters and apocalyptic environmental elements, and (3) Environmental wisdom values ??consisting of attitudes of love and concern for nature.